2018
DOI: 10.1186/s12957-018-1439-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients with metastatic spine tumors derived from lung cancer—a novel scoring system for predicting life expectancy

Abstract: BackgroundRecently, molecule-targeting and bone-modifying agents have improved the treatment outcomes of lung cancer-derived metastatic spine tumors. Therefore, the prognostic factors for such tumors were examined, and novel scoring systems for predicting the life expectancy of patients with such tumors were proposed.MethodsIn 207 patients with lung cancer-derived metastatic spine tumors (surgery 49; conservative therapy 158), we retrospectively examined the factors that influenced the post-treatment survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Renowned prognostic scoring systems (Bauer, Tokuhashi, Tomita, van der Linden, Sioutos, Katagiri, and NESMS) have been developed to assist clinicians and care providers in determining the survival prognosis of metastatic spine tumor patients for an optimal therapeutic choice [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . In contrast to this study, none of these scoring systems include demographic features such as age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Renowned prognostic scoring systems (Bauer, Tokuhashi, Tomita, van der Linden, Sioutos, Katagiri, and NESMS) have been developed to assist clinicians and care providers in determining the survival prognosis of metastatic spine tumor patients for an optimal therapeutic choice [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . In contrast to this study, none of these scoring systems include demographic features such as age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…found that previous chemotherapy was a significant prognostic factor [ 13 ], but was the sole non-significant factor per our multivariate analyses ( Table 2 ). A few studies found that treatment with molecularly targeted drugs is an important predictor of prognosis in patients with bone metastases arising from lung cancer [ 28 , 29 ]. The Katagiri score variable ‘primary tumor growth’ also evaluates whether lung cancer can be treated with molecularly targeted drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Even more prognosispredicting scoring systems appear in the literature which focus on metastases caused by one type of primary tumor (so we can get more precise prediction based on more specific information, e.g., histological categorization, molecular subtypes, specific targeted treatment options, etc.). Uei et al [27] designed a new system for estimating the outcome of spinal metastasis in patients with primary lung cancer, which also takes into account the possibility of tumor antigens and molecular target therapy.…”
Section: Discussionmentioning
confidence: 99%